(untitled) (Intent Research Scientific Journal, 2023)
The work is devoted to the study of the role of color in a costume. with color people always associate certain ideas, color associated with mood and well-being. Color in clothes is, first of all, a manifestation of national traditions, it forms taste, characterizes temperament, state of mind. The clothes chosen by a person reflect the psychological essence of the personality